Actuating NJ Trainers In Improving Organizational Leadership Quality Through In-House Training At The Nurul Jadid Islamic Boarding School - Muhammad Mushfi El Iq Bali; Zahiya Adiba (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2024)
This study aims to determine the actuated NJ Trainers in the field of quality Leadership in forming an effective organisation. This research took place at Pondok Pesantren Nurul Jadid Paiton Probolinggo. This data collection uses a qualitative case study approach. Acquisition of data through observation and interviews with Deputy Kasi Diklat and OSAT ORDA of the Development Bureau, the Head of NJ Trainer's, the head of Nurul Jadid Islamic Senior High School, the member of FKO Nurul Jadid and the head of HIMASYI who is under the auspices of Nurul Jadid Islamic Boarding School. Data analysis procedures are data collection, data presentation, data reduction, and conclusion making. The results showed that the Quality Leadership of the pesantren organisation includes: The leader has a very extraordinary strategy and concept to get to the high quality of the pesantren organisation through In-House Training. Able to develop organisational skills in seeking organisational experience in pesantren. This pattern is a good organizational contribution to the sustainability of Islamic boarding schools in the future transition era.